Analysis Trigonometry Learning Obstacles from Mathematical Literacy Perspective - Thasiro; Ruzai, Wan Nur Aqlili (Program Magister Pendidikan Matematika, Pascasarjana, Universitas Pasundan in collaboration with Asosiasi Guru Matematika Indonesia (AGMI) and Indonesian Mathematics Educators' Society (IMES), 2023)
The focus of this research is to examine the challenges that students face when attempting trigonometry questions in mathematical literacy. These learning obstacles need to be addressed in order to maximize the students' learning achievements. The trigonometry material that is presented in mathematical literacy includes various identities, such as the sum and difference of angles, double angle identity, beak angle identity, multiplication to addition identity, and addition to multiplication identity. Mathematical literacy is based on 5 indicators, namely (1) making mathematical models in the form of tables, pictures, graphs, diagrams, and mathematical expressions that make it easier to solve problems, (2) choosing and comparing strategies to obtain solutions, (3) writing answers in logical calculations, (4) use reasoning to associate information obtained from a problem with the concept that is owned, and (5) use or manipulate formulas or procedures in solving problems. In this research, a qualitative method was utilized to analyze the answers provided by students from class XI MIPA 6 SMAN 1 Palimanan. The findings of this study indicate that students face learning challenges in trigonometry when it comes to mathematical literacy, specifically in indicators (3), (4), and (5).